Some recommendations for the construction of walls using adobe bricks (2014)
This paper shows some results of the analysis of wall construction with adobe bricks, carried out in a pilot building in Villa Clara, Cuba. Our main objective was to obtain some construction recommendations to avoid the humidity due to capillarity. The recommendations deal with uprising speed of construction, adequate wall longitude, binding mortar between adobe bricks, adobe protection from weathering, etc.